The Adoption of Internet Banking: Clients' Perspective in Oman - Alraja, Mansour Naser; Salim, Badreldin F.; Uddin, Mohammad Ahmar; Yousoof, Mohammed (International Review of Management and Marketing, 2016)
Internet Banking enables clients to manage their accounts or carrying out their work related to the bank via the Internet, whether at home, office or from any place and at any time he/she desires to do. Hence, the main objective of our paper is to identify the adoption level of internet banking among the clients of Omani banks. Therefore, the technology acceptance Model (TAM) is utilized to examine effect of perceived usefulness, and perceived ease of use on clients' intention to adopt internet banking in Sultanate of Oman. To accomplish this goal a manual questionnaire was administered to collect the requested data to test the clients' intention to adopt internet banking. Multiple regression test was used to analyze the collected data and test the hypotheses of the paper. The findings show that the TAM model interpreted 56.3 % of the variance in clients' intention to adopt internet banking. Both constructs' (perceived usefulness, and perceived ease of use) have a significant influence on clients' acceptance of internet banking. The results of the study are discussed. Keywords: Internet Banking, TAM, Perceived Ease of Use, Perceived Usefulness JEL Classification: G2